Comparação entre soluções irrigadoras na endodontia: clorexidina x hipoclorito de sodio - Pretel, Hermes (2011)
The objective of this review was reporting an overview about the properties of two irrigating solutions, solution of sodium hypochlorite and chlorhexidine, used in the treatment of root canals. A solution must submit irrigating antimicrobial action, dissolve waste tissue, promote wetting to facilitate the instrumentation, and present biocompatibility with the adjacent tissues. The sodium hypochlorite used in different concentrations has been the solution of choice among professionals by presenting antimicrobial action and act as a solvent tissue. However, today, chlorhexidine has been widely used as an irrigating solution due to specific properties that enable its use, such as substantivity, antimicrobial effectiveness, and low toxicity. Thus the solution of chlorhexidine with different concentrations is presented as an alternative to irrigating solution for the treatment of root canals.